Trends on environmental accounting in the field of research in the last five years (Revista "Boletín el Conuco", 2021)
The eagerness to investigate about environmental accounting has led several researchers to unveil knowledge in relation to this field of accounting. The main objective of the research is to determine trends and advances in environmental accounting in the research scenario at the national and international level. The proposed research approach is qualitative descriptive; For the purpose of gathering the information, a content analysis format is designed and applied to identify, classify and examine the qualitative data obtained from the databases of indexed journals and repositories.
Keywords: environment; costs; control; sustainable development